If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3y = -12 Solving 4 + 3y = -12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3y = -12 + -4 Combine like terms: 4 + -4 = 0 0 + 3y = -12 + -4 3y = -12 + -4 Combine like terms: -12 + -4 = -16 3y = -16 Divide each side by '3'. y = -5.333333333 Simplifying y = -5.333333333
| -17=4x+12-9x | | 3x-5/x-1=3x-2/x+2 | | -0.4p=0.2p+9 | | -7x+1=6 | | 8/3-2 | | 7f-8=2 | | 2x5/2+5x3/2=7x1/2 | | 7/12+1/4 | | 13/85.8 | | -c+4=-2c | | x/2+5=-12 | | -8x-2=24-9x | | 45/34a=23.3+46a | | 5.6q-3.4-4.9q=0.3q-2.3 | | 3-3(3n-3)=39 | | 3a+9b+-5a+15b= | | 5/9=h/30 | | -8x-2=24-9 | | 8+16p^2=33 | | 85.5/13 | | 9x-4=5x+4 | | 4t+5=-10+t | | v-15=9 | | 63(x-3)=9(x+3) | | 2(x+4)=3x+5 | | 7a+-9b+3a+9b= | | 5x+9=-3 | | O(5)=2(5)-1 | | 8m-7=21+m | | 12q-7=-3q+8 | | -4q=9-5q | | 20a/30+6/30=35/30 |